PENGARUH KOMPENSASI, LINGKUNGAN KERJA DAN BUDAYA ORGANISASI TERHADAP LOYALITAS DAN KINERJA KARYAWAN (Studi Pada Karyawan STIE-AUB Surakarta) - Triono, BRM. Suryo (-)
The purpose of this study is to examine the effect of compensation, work environment and organizational culture on employee loyalty and performance Result of t test that is Organizational Culture have positive and significant influence to Employee Loyalty, Compensation have positive effect and not Significant to Employee Loyalty And Work Environment negatively and Not Significant to Employee Loyalty. Organizational Culture has a positive and significant impact on Performance, And While Compensation and Work Environment is Positive and Not Significant to Employee Performance and Loyalty is negative and not Significant to Performance.Value of R2 square total equal to 0,5141 which mean employee performance variable explained by compensation, work environment, and organizational culture with job loyalty as interverning variable equal to 51,41% and the rest equal to 48,59% explained other factor outside research model. Effect of the most effective and dominant variable in order to improve the performance of employees STIE AUB Surakarta is a variable of organizational cultureKeywords             : Compensation, Work environment, Organizational culture, Loyalty,        Employee performance